(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Wave energy is a significant and relatively untapped source of renewable energy [1], which can considerably contribute to decarbonization. The oscillating-water-column (OWC) [2] is one of the most promising wave energy converters (WECs) for harnessing wave power, especially due to its relatively simple operating principle and the fact that all the moving parts are above the water level. To improve the commercial viability of WECs, the levelised cost of energy should be minimised and, to this end, comprehensive control strategies to maximise electric energy are essential [3]. Due to the important issue of turbine efficiency, the vast majority of OWC control strategies [4] focus on a simplified control objective, namely turbine efficiency maximisation. While maximising turbine efficiency is a primary focus of OWC control strategies, it is important to note that rotational speed control impacts generator performance. Additionally, for Wells turbines [5], rotational speed control also affects the hydrodynamic performance, specifically the wave-to-pneumatic energy conversion process. Therefore, Wells turbine rotational speed should be ideally modulated to improve the overall wave-to-wire (W2W) efficiency of the OWC system [6], rather than just turbine efficiency. In this paper, a control strategy for maximising W2W efficiency of a fixed OWC WEC equipped with a Wells turbine is proposed. A schematic of the W2W power train of the OWC WEC considered in this paper is depicted in Figure 1. The proposed control strategy comprises of two parts. Firstly, a `complete’ setpoint, which considers the entire OWC W2W model (WEC hydrodynamics, Wells turbine, and generator dynamics), is derived. Secondly, a Lyapunov-based nonlinear controller is designed to track the aforementioned setpoint. Preliminary results from the numerical simulation show that, in comparison to the somewhat traditional turbine efficiency maximising control approach, the proposed W2W control strategy leads to a significant improvement in the electric energy production for all the considered sea states.